Interdependence between Oscillations of the Stratospheric Aerosol Layer Peaks and Different Types of Clouds - Pratibha B. Mane (Current Advances in Geography, Environment and Earth Sciences Vol. 3, 2022)
Aerosol measurements were taken using a newly constructed Semiautomatic Twilight Photometer at Kolhapur (16\(^°\)42\(^′\)N, 74\(^°\)14\(^′\)E). The system is a ground-based passive remote sensing technology that is simple and affordable but extremely sensitive. The main objective of the study is, to find out interdependence between oscillations of Junge layer peak (its altitude & Aerosol Number Density per cm3 (AND)) and different types of clouds. One attempt is made to look into the relationship between stratospheric aerosol layer peak oscillations and different types of clouds. For each observational day, the AND values for the Junge layer peaks were determined. In addition, the graph between AND at the summit of the Junge layer and day numbers was compared to High, Medium, and Low-level clouds. There was also a yearly change in the Jung layer peak’s altitude. The annual fluctuation in the height of the Jung layer peak and the AND of the Junge layer peak exhibited an inverse phase relationship.